Exploring the Psychological Realities of U.S Women Soldiers during the Iraq War in Sand Queen Novel - Assist. Lecturer. Estabraq Ali Alwazzan (Journal of College of Education, 2024)
When women are working in conflict zones, they do a variety of tasks that are not only significant but also often ignored. In these roles, women are responsible for a diverse array of responsibilities, including those of journalists, nurses, medics, peacekeepers, and soldiers, among others. Women’s work is important as it has advantages such as giving services to people and representing the element of war peace. On the contrary, they face some problems, for instance; crime, the use of violence against gender, and kidnap. Women are used to having the main responsibilities towards their home and children. The characteristics of men are having authority and complicated discussion. Historically, women have great jobs which is female soldiers in the place of war. Furthermore, communities feel doubt about joining the women in the military but within the time it had started to change this idea by thinking that women have multi-skills which is based on service and security requirements. Also, governments have started to pass laws to allow women to do their work throughout the war zone. American women soldiers played a part in participating in the Iraq War in 2003 regardless of the use of violence against women. This study examines violence against American soldiers in Iraq and the strategies for addressing the psychological consequences of this kind of violence. The Sand Queen novel (2011) by Helen Benedict will set a literary foundation of analysis by employing the Binary Model of GBV and Trauma Theory. The results showed that violence against women in war is unquestionably deadly and has far-reaching implications for people, communities, and civilizations. Policymakers and military organizations may design effective policies to safeguard the safety and well-being of female troops by studying the dynamics of violence against women in the military